Nonlinear behavior of RF Bulk Acoustic Wave cascaded components at high input power - Chauhan, Vikrant; Mayer, Markus; Huck, Christian; Pitschi, Maximilian; Weigel, Robert; Hagelauer, Amelie Marietta (IEEE Asia-Pacific Microwave Conference (APMC), 2016)
At high frequency, Bulk Acoustic Wave (BAW) devices are mainly used for filtering in front-ends of modern mobile transceivers. Furthermore, the transmitter filters are usually used at high input power levels of up to 33 dBm, which lead to nonlinearity and self-heating within the filter. In this work a thermo-electro-mechanical Mason model combined with a 3-dimensional electromagnetic finite element method (3D EM FEM) is used for modeling the nonlinear behavior of different BAW components. The impedance curve, filter response, second harmonics as well as inter-modulation distortion (IMD) of cascaded BAW resonators and filters due to the nonlinearities are explained. With the aid of the developed method, different cascading approaches for optimizing the nonlinear behavior are shown. Measurements of BAW components up to second order harmonics have been carried out using a nonlinear vector network analyzer (NVNA).
Keywords: Resonators; Harmonic analysis; Power harmonic filters; Power measurement; Frequency measurement; Area measurement; Bulk acoustic wave devices